High-Throughput Approach for Evaluating Antibacterial Activity of Fish Epidermal Mucus: Antibacterial Activity of Fish Epidermal Mucus - Sivam, Visnuvinayagam; Cheriyan, Subie Thankam; Chandran, A.; Nilavan, S. E.; Murugadas, V.; Joseph, T. C. (Fishery Technology, 2025)
Fish epidermal mucus (FEM) is a source of antimicrobial peptides (AMP) that play an important role in the innate immunity of fish. Currently, there are no simple and quick protocols for screening FEM for antimicrobial activity. The present work describes the optimization of a modified optical density reduction (MODR) method to screen the FEM for antibacterial activity against various bacteria within 8 h. Reduction in optical density values in the bacteria compared with positive control suggest FEM sample exhibits antibacterial activity. The MODR approach is a low-cost, rapid and solvent-free method, and can be used to screen the FEM for potential antibacterial activity.